WITHDRAWN: The Palaeocene Cerro Munro tonalite intrusion (Chubut Province, Argentina): A plutonic remnant of explosive volcanism?. (October 2017) - Rodríguez, C.; Aragón, E.; Castro, A.; Pedreira, R.; Sánchez-Navas, A.; Díaz-Alvarado, J.; D´Eramo, F.; Pinotti, L.; Aguilera, Y.; Cavarozzi, C.; Demartis, M.; Hernando, I.R.; et al.
Abstract : The publisher regrets that an error occurred which led to the premature publication of this paper. This error bears no reflection on the article or its authors. The publisher apologizes to the authors and the readers for this unfortunate error in Journal of South American Earth Sciences, 78C (2017) 30 – 60, http://dx.doi.org/10.1016/j.jsames.2017.06.002 . The article has therefore been withdrawn. The full Elsevier Policy on Article Withdrawal can be found athttps://www.elsevier.com/about/our-business/policies/article-withdrawal